Perceived Discrimination and Subjective Well-being in Chinese Migrant Adolescents: Collective and Personal Self-esteem As Mediators - Jia, Xuji; Liu, Xia; Shi, Baoguo (Frontiers in Psychology, 2017)
This study aimed to examine whether collective and personal self-esteem serve as mediators in the relationship between perceived discrimination and subjective well-being among Chinese rural-to-urban migrant adolescents. Six hundred and ninety-two adolescents completed a perceived discrimination scale, a collective self-esteem scale, a personal self-esteem scale, and a subjective well-being scale. Structural equation modeling was used to test the mediation hypothesis. The analysis indicated that both collective and personal self-esteem partially mediated the relationship between perceived discrimination and subjective well-being. The final model also revealed a significant path from perceived discrimination through collective and personal self-esteem to subjective well-being. These findings contribute to the understanding of the complicated relationships among perceived discrimination, collective and personal self-esteem, and subjective well-being. The findings suggest that collective and personal self-esteem are possible targets for interventions aimed at improving subjective well-being. Programs to nurture both the personal and collective self-esteem of migrant adolescents may help to weaken the negative relationships between perceived discrimination and subjective well-being.